Attenuation of short wavelengths alters sleep and the ipRGC pupil response - Ostrin, Lisa A.; Abbott, Kaleb S.; Queener, Hope M. (Ophthalmic & physiological optics, 2017)
Purpose Exposure to increasing amounts of artificial light during the night may contribute to the high prevalence of reported sleep dysfunction. Release of the sleep hormone melatonin is mediated by the intrinsically photosensitive retinal ganglion cells (ipRGCs). This study sought to investigate whether melatonin level and sleep quality can be modulated by decreasing night‐time input to the ipRGCs. Methods Subjects (ages 17–42, n = 21) wore short wavelength‐blocking glasses prior to bedtime for 2 weeks. The ipRGC‐mediated post illumination pupil response was measured before and after the experimental period. Stimulation was presented with a ganzfeld stimulator, including one‐second and five‐seconds of long and short wavelength light, and the pupil was imaged with an infrared camera. Pupil diameter was measured before, during and for 60 s following stimulation, and the six‐second and 30 s post illumination pupil response and area under the curve following light offset were determined. Subjects wore an actigraph device for objective measurements of activity, light exposure, and sleep. Saliva samples were collected to assess melatonin content. The Pittsburgh Sleep Quality Index (PSQI) was administered to assess subjective sleep quality. Results Subjects wore the blue‐blocking glasses 3:57 ± 1:03 h each night. After the experimental period, the pupil showed a slower redilation phase, resulting in a significantly increased 30 s post illumination pupil response to one‐second short wavelength light, and decreased area under the curve for one and five‐second short wavelength light, when measured at the same time of day as baseline. Night time melatonin increased from 16.1 ± 7.5 pg mL−1 to 25.5 ± 10.7 pg mL−1 (P < 0.01). Objectively measured sleep duration increased 24 min, from 408.7 ± 44.9 to 431.5 ± 42.9 min (P < 0.001). Mean PSQI score improved from 5.6 ± 2.9 to 3.0 ± 2.2. Conclusions The use of short wavelength‐blocking glasses at night increased subjectively measured sleep quality and objectively measured melatonin levels and sleep duration, presumably as a result of decreased night‐time stimulation of ipRGCs. Alterations in the ipRGC‐driven pupil response suggest a shift in circadian phase. Results suggest that minimising short wavelength light following sunset may help in regulating sleep patterns.